The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/advs.202205451
|View full text |Cite
|
Sign up to set email alerts
|

Podocalyxin‐Like Protein 1 Regulates Pluripotency through the Cholesterol Biosynthesis Pathway

Abstract: Deciphering signaling mechanisms critical for the extended pluripotent stem cell (EPSC) state and primed pluripotency is necessary for understanding embryonic development. Here, a membrane protein, podocalyxin-like protein 1 (PODXL) as being essential for extended and primed pluripotency, is identified. Alteration of PODXL expression levels affects self-renewal, protein expression of c-MYC and telomerase, and induced pluripotent stem cell (iPSC) and EPSC colony formation. PODXL is the first membrane protein re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…It has been shown that the rigidification of the PM precedes or coincides with downregulation of gene expression programs that stabilize the pluripotent state in PSCs, suggesting that a decrease in membrane fluidity may prime PSCs to exit from pluripotency. Consistent with the notion that maintenance of membrane fluidity contributes to stem cell maintenance, enzymes in the cholesterol biosynthesis pathways have been shown to be expressed at higher levels in PSCs, thereby increasing membrane cholesterol content and fluidity [78,79]. Importantly, the inhibition of cholesterol production in PSCs accelerates their exit from pluripotency, as indicated by the rapid downregulation of stem cell marker alkaline phosphatase [78].…”
Section: Cholesterol Transporters (Abca1 and Abcg1)mentioning
confidence: 68%
“…It has been shown that the rigidification of the PM precedes or coincides with downregulation of gene expression programs that stabilize the pluripotent state in PSCs, suggesting that a decrease in membrane fluidity may prime PSCs to exit from pluripotency. Consistent with the notion that maintenance of membrane fluidity contributes to stem cell maintenance, enzymes in the cholesterol biosynthesis pathways have been shown to be expressed at higher levels in PSCs, thereby increasing membrane cholesterol content and fluidity [78,79]. Importantly, the inhibition of cholesterol production in PSCs accelerates their exit from pluripotency, as indicated by the rapid downregulation of stem cell marker alkaline phosphatase [78].…”
Section: Cholesterol Transporters (Abca1 and Abcg1)mentioning
confidence: 68%
“…PODXL is an anti‐adhesive glycoprotein, highly expressed on the membrane of ESC and iPSC (Koch et al., 2008 ; Larrucea et al., 2008 ). The expression level of PODXL affects self‐renewal, protein expression of c‐MYC and telomerase, and iPSC colony formation (Chen et al., 2022 ). SSEA4 is a marker of immaturity and is highly expressed by undifferentiated human embryonic stem cells and downregulated during differentiation (Guan et al., 2022 ; International Stem Cell Initiative et al., 2007 ; Takahashi et al., 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that 3D culture and spheroid formation are often used to select for cancer-initiating cells [ 12 , 13 ], our data in conjunction with epidemiological/clinical data may point to a role for cholesterol in cancer progression which was not uncovered in previous in vitro studies using 2D systems and high statin doses. While there are currently no reports on the influence of the cholesterol pathway on 3D spheroid formation of normal, non-cancerous stem cells, in the few reports using standard 2D culture, it does appear that perturbations of this pathway can affect the stemness/differentiation capacity of both adult stem cells as well as pluripotent stem cells [ 51 , 52 , 53 ]. Our data demonstrates the importance of the cholesterol synthesis pathway in modulating cell-specific fates as well as 3D spheroid formation capacity.…”
Section: Discussionmentioning
confidence: 99%